ICSID 2015 Annual Report - International Centre for Settlement of Investment Disputes (World Bank Group, Washington, DC, 2015)
2015 marked the ICSID Convention’s 50th anniversary and has been an opportunity to review and celebrate the accomplishments of ICSID’s first 50 years. Today ICSID is the premier international investment arbitration facility in the world, with the ICSID Convention ratified by 151 members and signed by a further eight States. The Centre’s activities in fiscal year 2015 are presented in detail in this report.